Madelung disease with postoperative priapism and multiple venous thromboses: case report and literature review - Guo, Linfen; Li, Wei; Xu, Xuewen; Xiao, Haitao (Frontiers in Cardiovascular Medicine, 2024)
Madelung disease is an uncommon metabolic disorder of uncertain pathogenesis, distinguished by the symmetric accumulation of nonencapsulated adipose tissue within the subcutaneous layer of the neck, abdomen, thighs, and other anatomical regions. This condition has been tightly connected with comorbidities including diabetes, dyslipidemia, hyperuricemia, hypothyroidism, and adrenal dysfunction, as well as sensory, motor, and autonomic polyneuropathy. The prevalence of Madelung disease is conspicuously higher in Mediterranean and Eastern European, with a distinct scarcity within the Asian population. Surgical interventions involving lipectomy and liposuction represent the foremost and most efficacious treatment approach. Herein, we present a case encompassing type II Madelung disease featuring bilateral thighs adipose tissue accumulation. The patient exhibited unexplained priapism alongside multiple venous thrombosis during four surgical interventions. The infrequent manifestation of postoperative hypercoagulability in patients of Madelung disease merits broad attention, owing to the potentiality for extensive venous thrombosis and consequential severe outcomes such as pulmonary embolism or cerebral infarction arising from thrombus dislodgment. Building upon this clinical scenario, we systematically documented the clinical manifestations and disease progression in this patient, meticulously analyzed the causes of complications, and proposed targeted preventive measures. Additionally, we conducted a comprehensive review of the relevant literature to summarize the clinical and epidemiological features of Madelung disease and to elucidate its mechanisms. This study will provide a valuable reference for future clinical treatments and mitigate perioperative complications of Madelung disease.